2021
DOI: 10.1097/htr.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy After Concussion: A Clarion Call for Attention?

Abstract: Objective: Emerging research shows that women who sustain a mild traumatic brain injury, also termed concussion, have a higher risk of menstrual irregularities and sexual dysfunctions. However, no research exists on how these reproductive disruptions affect women's subsequent pregnancies. The objective of this study was to evaluate pregnancy outcomes after concussion in a cohort of reproductive-aged women (aged 18-45 years), 24 months post-injury. We hypothesized that, compared with their extremity-injured pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(165 reference statements)
0
5
0
Order By: Relevance
“…Women older than age 45 years were excluded to avoid the hormonal irregularities associated with the menopausal transition. [21][22][23] To capture naturally cycling women, we excluded women who were menopausal or postmenopausal before the pandemic, had undergone hysterectomy, were currently pregnant, were less than 3 months postpartum, were currently receiving exogenous glucocorticoids, had undergone infertility treatments before the pandemic, or were currently taking hormonal birth control.…”
Section: Methodsmentioning
confidence: 99%
“…Women older than age 45 years were excluded to avoid the hormonal irregularities associated with the menopausal transition. [21][22][23] To capture naturally cycling women, we excluded women who were menopausal or postmenopausal before the pandemic, had undergone hysterectomy, were currently pregnant, were less than 3 months postpartum, were currently receiving exogenous glucocorticoids, had undergone infertility treatments before the pandemic, or were currently taking hormonal birth control.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings add to emerging studies suggesting that women with TBI may experience impairments to their reproductive health, including the recent study-"Pregnancy After Concussion: A Clarion Call for Attention?" 14 -which found that women with a concussion had a reduced incidence of pregnancy compared with women without concussion. Taken together, our new findings highlight the need for future research to inform increased understanding regarding preexisting risk and associated negative reproductive health outcomes among women with TBI using longitudinal and prospective epidemiological and biological data.…”
Section: E173mentioning
confidence: 99%
“…[5][6][7][8][9] Nevertheless, findings from these studies indicate that TBI may have unique biological and psychosocial consequences for women including a greater risk for sexual dysfunction 10 and amenorrhea and irregular menstrual cycles, possibly due to sustained damage to the pituitary gland 6,7,[11][12][13] and the hypothalamic-pituitary-gonadal axis. 14 A recent study of women seeking care in the emergency department for a concussion, compared with those seeking care for extremity injuries, found that pregnancy incidence 24 months postinjury was 76% lower for women with a concussion than for those without. 14 Women with TBI have also reported reduced utilization of obstetrician/gynecologist (OB/Gyn) services and family physician/midwife services postinjury compared with preinjury, which may have consequences for their reproductive health.…”
Section: Drs Akobirshoev and Mitramentioning
confidence: 99%
See 2 more Smart Citations